APPLICATION OF ACCOUNTING INFORMATION SYSTEMS IN FINANCIAL MANAGEMENT IN CILEGON CITY HOUSEHOLD SMEs - Mochamad Fahru Komarudin (International Journal of Economy, Education and Entrepreneurship, 2023)
The application of an accounting information system (SIA) to MSMEs can provide significant benefits in financial management. However, with advances in information and communication technology, more and more SMEs are starting to switch to using an accounting information system (AIS) to simplify their financial management. The use of SIA will help MSMEs to save time and costs spent on financial management, and make it easier to make more informed business decisions because they have easier and faster access to company financial information. In this study, it was found that SIA can increase the effectiveness, efficiency, and accuracy in storing financial information needed by MSME owners in making decisions. Several other benefits of applying SIA to MSMEs. Overall, the application of SIA to MSMEs can help improve financial management effectively and efficiently, and can provide significant benefits for companies in the long term. However, there are still many MSMEs that experience difficulties in implementing SIA due to limited funds, limited human resources, and a lack of understanding about the benefits of using SIA. Therefore, the government and related institutions need to provide guidance and support to SMEs in terms of developing and implementing an SIA in order to improve the quality and effectiveness of corporate financial management